Anatomical Variations of the Trapezius Muscle: Biomechanical and Functional Implications - Puchalska-Sarna, Anna; Lenart-Domka, Ewa; Trzeciak, Jadwiga; Domino, Grzegorz; Sarna, Michał; Walicka-Cuprys, Katarzyna (Technium BioChemMed, 2026)
Abstract The trapezius muscle is a large, superficial muscle of the posterior thoracic region that plays a fundamental role in scapular stabilization, upper limb movement, and cervical spine biomechanics. Numerous anatomical studies have demonstrated that the trapezius exhibits considerable morphological variability in its origin, insertion, fiber arrangement, innervation patterns, and muscular segmentation. Different researchers have reported variations including accessory muscle slips, partial absence of specific portions (particularly the lower or middle fibers), asymmetry between sides, atypical attachments to the clavicle or scapula, and deviations in the course of the spinal accessory nerve. Some cadaveric and imaging-based studies have also described variations in muscle thickness, fascicle orientation, and aponeurotic structure, which may influence force transmission and scapulothoracic mechanics. From a biomechanical perspective, these anatomical differences may alter scapular kinematics, shoulder elevation patterns, and load distribution across the cervical and thoracic spine. Functional implications include potential predisposition to shoulder impingement, scapular dyskinesis, neck pain syndromes, and altered postural control. Furthermore, anatomical variability has important clinical relevance in surgical procedures, reconstructive techniques, nerve repair, and rehabilitation planning. Overall, the available literature suggests that anatomical variations of the trapezius muscle are more common than traditionally assumed and may significantly influence both normal movement patterns and pathological conditions. Recognition of these variations is essential for anatomists, clinicians, surgeons, and physiotherapists to ensure accurate diagnosis, effective treatment, and optimized functional outcomes.